Complexidade, os Limites do Controlo - FAUSTINO, Carlos (2013)
This paper aims at developing the concept of Complexity within what could be called ‘Generative Art’. After laying out the limits of Algorithmic Complexity and Effective Complexity, including practical examples, a critical position will be developed on the two opposite poles in contrast with an eventual intermediate point. On the one hand, a structured position with rules that are essentially based on symmetry; on the other, complete randomness. The pole that corresponds to complete randomness will be taken into fuller consideration – as contemporary artists, such as John Cage, have chosen this factor more often.